Systematic theology, v. 1 - Tillich, Paul, 1886-1965, (Johannes Oskar) (Herts, U.K. Nisbet, 1951)
Contents : Part 1 : Reason and revelation; Part 2 : Being and God. Includes bibliographical references and index.
Donated by the Adelaide Assemblies, May, 1964
Keywords: Theology, doctrinal